An equality-growth tradeoff - Lane Kenworthy (Luxembourg Income Study (LIS), 2003)
For a long time conventional wisdom held that income inequality enhances investment and work incentives and thereby is good for economic growth. In the 1990s this view was turned on its head, as a number of empirical analyses found an association between inequality and slower growth across large samples of mainly less developed nations. Researchers also identified various causal paths through which inequality might reduce growth. Recently, several studies focusing on rich countries have discovered an apparent growth-enhancing effect of inequality, consistent with the older view. My examination of 15 affluent countries over the 1980s and 1990s suggests no general tendency for inequality to influence economic growth in either direction. The same is true for the U.S. states in these two decades. Post-World War II longitudinal trends in the United States also offer no indication that inequality has had an effect on growth.
Keywords: 330; Einkommensverteilung; Haushaltseinkommen; Armut; Wirtschaftswachstum; Schätzung; USA